Botox Optimization Algorithm: A New Human-Based Metaheuristic Algorithm for Solving Optimization Problems - Hubálovská, Marie; Hubálovský, Štěpán; Trojovský, Pavel (Biomimetics (Basel, Switzerland), 2024)
This paper introduces the Botox Optimization Algorithm (BOA), a novel metaheuristic inspired by the Botox operation mechanism. The algorithm is designed to address optimization problems, utilizing a human-based approach. Taking cues from Botox procedures, where defects are targeted and treated to enhance beauty, the BOA is formulated and mathematically modeled. Evaluation on the CEC 2017 test suite showcases the BOA's ability to balance exploration and exploitation, delivering competitive solutions. Comparative analysis against twelve well-known metaheuristic algorithms demonstrates the BOA's superior performance across various benchmark functions, with statistically significant advantages. Moreover, application to constrained optimization problems from the CEC 2011 test suite highlights the BOA's effectiveness in real-world optimization tasks.
Keywords: optimization; human-inspired; metaheuristic; Botox; exploitation; exploration